Direct medical costs associated with the extrahepatic manifestations of hepatitis C infection in Europe. Issue 7 (30th March 2018) - Cacoub, P.; Buggisch, P.; Carrión, J. A.; Cooke, G. S.; Zignego, A. L.; Beckerman, R.; Younossi, Z.
Summary: Hepatitis C virus (HCV) infection is a systemic disease associated with both hepatic and extrahepatic manifestations. The burden associated with the hepatic manifestation of HCV infection has been well documented in Europe, although that of HCV extrahepatic manifestations remains unknown. In this study, we estimated the annual direct medical costs associated with HCV extrahepatic manifestations in five European countries. A previously validated economic model was used to estimate the annual direct medical cost associated with HCV extrahepatic manifestations. Global excess prevalence of extrahepatic manifestations in HCV patients relative to that in non‐HCV patients was obtained from a recent meta‐analysis. Per‐patient per‐year inpatient, outpatient and medication costs to treat each extrahepatic manifestation were from the literature, national databases or expert opinion if unavailable otherwise. All costs were adjusted to 2016 euros (€). The overall direct medical costs associated with HCV extrahepatic manifestations were calculated by multiplying the total per‐patient per‐year costs of each by the respective excess prevalence rates and then by the size of the HCV‐infected population in each country. Treatment impact with direct‐acting antivirals (DAAs) was explored using HCV extrahepatic manifestations excess prevalence rates among cured patients compared to untreated HCV patients, as sourced from a meta‐analysis. The total annual direct medical cost associated with HCV extrahepatic manifestations was estimated to be 2.17 billion euro (€), with a per‐HCV‐patient cost ranging from €899 to €1647 annually. DAA treatment was projected to result in cost savings of €316 million per year. We find that the annual economic burden of extrahepatic manifestations is significant and may be partly mitigated by treatment with DAAs.